Effectiveness and legality of dispute resolution mechanisms under rera: Adjudicating officers and appellate tribunals - Dr. Madhulika Mishra; Prof. (Dr.) Pradeep Kulshreshtha, Ms. Arushi Sharma; Mr. Yogesh Chandra Gupta, Mrs. Varalika S. Parashar; Mr. Sourabh Batar (Journal of Informatics Education and Research, 2025)
The Real Estate Act of 2016 represents a significant transformation in the Indian real estate sector by introducing a clear regulatory mechanism to address consumer’s grievances and ensure expeditious resolutions (Raju, 2007). This law also provides for the adjudicating officers and the appellate tribunals which are crucial mechanisms for resolving the disputes arising among the promoters, allotters, and the real estate agents. The intent is place the industry under the needful expose-plus-control spotlight (Gould & Linneman, 2008). The success of the Act largely depends on the ability of these quasi-judicial bodies to manage complaints and enforce the law in an efficient, fair, and legal way (Ndekugri & Russell, 2005). This article will explore in practical terms the stand of different dispute resolution institutions, focusing on the powers, practice and the general impact of these on the estate industry. The success/ability of RERA to achieve its avowed objectives largely depends on the proper and efficient functioning of the adjudicating officers and the appellate tribunals.